The halophilic bacteria Gracilibacillus dipsosauri GDHT17 alleviates salt stress on perennial ryegrass seedlings - Li, Xiangying; Zheng, Jinyuan; Wei, Wei; Gong, Zifan; Liu, Zhenyu (Frontiers in Microbiology, 2023)
Adverse abiotic environmental conditions including excess salt in the soil, constantly challenge plants and disrupt the function of plants, even inflict damage on plants. Salt stress is one of the major limiting factors for agricultural productivity and severe restrictions on plant growth. One of the critical ways to improve plant salt tolerance is halotolerant bacteria application.A halophilic bacterium strain GDHT17, was isolated from saline soil, which grows in the salinities media with 1.0%, 5.0%, and 10.0% (w/v) NaCl, and identified as Gracilibacillus dipsosauri through classical bacteriological tests and 16S rRNA analysis. Perennial ryegrass (Lolium perenne L) was used in this study to evaluate the potential effect of G. dipsosauri GDHT17 on the plant under salt stress. Inoculating GDHT17 can significantly promote ryegrass's seedling height and stem diameter and increase the root length, diameter, and surface area at different salt concentrations, indicating the significant salt stress alleviating effect of GDHT17 on the growth of ryegrass. The alleviating effect on roots growth showed more effective, especially on the root length, which increased significantly by 26.39%, 42.59%, and 98.73% at salt stress of 100 mM, 200 mM, and 300 mM NaCl when the seedlings were inoculated with GDHT17. Inoculating GDHT17 also increases perennial ryegrass biomass, water content, chlorophyll and carotenoid content under salt stress. The contents of proline and malonaldehyde in the seedlings inoculated with GDHT17 increased by 83.50% and 6.87%, when treated with 300 mM NaCl. GDHT17-inoculating maintained the Na+ /K+ ratio in the salt-stressed ryegrass. The Na+/K+ ratio decreased by 26.52%, 6.89%, and 29.92% in the GDHT17-inoculated seedling roots treated with 100 mM, 200 mM, and 300 mM NaCl, respectively. The GDHT17-inoculating increased the POD and SOD activity of ryegrass seedlings by 25.83% and 250.79%, respectively, at a salt stress of 300 mM NaCl, indicating the properties of GDHT17, improving the activity of antioxidant enzymes of ryegrass at the salt-stress condition. Our results suggest that G. dipsosauri GDHT17 may alleviate salt stress on ryegrass in multiple ways; hence it can be processed into microbial inoculants to increase salt tolerance of ryegrass, as well as other plants in saline soil.